Disseminated herpes simplex virus 2 as a complication of pregnancy - Bougioukas, Lauren (IDCases, 2021)
Disseminated herpes simplex virus 2 (HSV-2) infection, is a rare but devastating infection in pregnancy women. We present the case of a 30-year-old gravida 3, para 2−0-0−2, at 26 weeks 2 days gestation who presented with eleven days of vague and indolent symptoms before a diagnosis of disseminated HSV-2 infection with associated hepatitis was made. While the patient clinically improved with empiric acyclovir treatment, possibility of significant harm to the fetus remained, and the patient request elective termination. The authors review the epidemiology, diagnosis, treatment, and prognosis of disseminated HSV-2 infection in pregnancy.